Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi terhadap Organizational Citizenship Behavior Pegawai - Erna, Erna; Fajar, Mustaina (Jurnal Metaverse ADPERTISI, 2026)
This research analyzes the influence of transformational leadership style and organizational culture on Organizational Citizenship Behavior (OCB) among employees of the Makassar City Education Office. A quantitative approach with explanatory research design was applied to 152 respondents (civil servants and PPPK) using Likert scale questionnaires and multiple linear regression analysis through SPSS 26. The results show: (1) Transformational leadership has a positive and significant effect on OCB (β₁ = 0.387, t = 5.234, p = 0.000); (2) Organizational culture has a positive and significant effect on OCB as the dominant factor (β₂ = 0.512, t = 7.891, p = 0.000); (3) Both variables simultaneously have a significant effect on OCB (F = 52.673, p = 0.000) with R² = 52.3%. Organizational culture has a stronger influence than transformational leadership in shaping extra-role behavior among public sector education employees. The combination of both factors explains 52.3% of OCB variation, with the remainder influenced by other variables. MLQ leadership training, CORE culture internalization program, and OCB indicator integration into ASN performance assessment (SKP). Future research is suggested to test organizational commitment mediation using SEM.